The effect of shadow conditions on stomatal characters of several plants used in landscape design - Sevik, Hakan; Cetin, Mehmet; Yigit, Nurcan; Aricak, Burak; Ozturk, Sevgi; Ayse Kalayci Onac; Inci Sevinc Kravkaz Kuscu (GSC Online Press, 2021)
The present study aims to determine the changes in stomatal characters of several plants depending on the shadow conditions. Within this scope, the leaf samples were collected from Platanus orientalis, Cercis siliquastrum, Eonymus japonica, Cotoneaster franchettii, and Buxus sempervirens species grown in open spaces. Scales images of leaf samples were taken using Scanning Electron Microscope and measurements were performed on these images in order to determine the micro-morphological characteristics such as stoma length (µm), stoma width (µm), pore opening length (µm), and pore opening width (µm) in the statistical analyses. The changes of these characteristics depending on the species, individuals, and shadow conditions were determined. The results showed that the differences in stomatal characteristics were statistically significant only between the individuals, whereas the effects of light and individual were statistically non-significant.
Keywords: Stoma; Stomatal Characteristics; Light; Micromorphology; 15. Life on land